EXTERNAL AUDIT QUALITY MEMODERASI PENGARUH ANTARA FUNGSI INTERNAL AUDIT DENGAN EARNINGS MANAGEMENT - Aqilla Delveoni Fadia (2022)
This research is using quantitative study aimed to see the effect of internal audit function proxied by size, expertise, and certification on the real earnings management with the moderating role of external audit quality and profitability, leverage, and firm size as control variables. Real earnings management is measured using the model from Zang (2012), namely the sum of abnormal discretionary expenses and abnormal production costs. The data used is secondary data sourced from the annual reports of non-financial companies listed on the Indonesia Stock Exchange in 2018-2020. The total sample used was 519 samples and analyzed using the STATA statistical test tool. The results showed that the size and expertise of internal audit had a significant negative effect on earnings management, while internal audit certification had a significant positive effect. The moderating role of external audit quality in strengthening the effect of internal audit size on real earnings management can be proven, but external audit quality has been proven to weaken the effect of internal audit expertise and certification on real earnings management.